2019
DOI: 10.2147/dddt.s196075
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dexmedetomidine for the prevention of emergence delirium and postoperative behavioral changes in pediatric patients with sevoflurane anesthesia: a double-blind, randomized trial</p>

Abstract: ObjectivesEmergence delirium (ED) is a common neurologic complication that can not only distress children and their families in the early postanesthetic period, but can also have adverse effects on children in the long-term. This study aimed to investigate the effects of single-dose dexmedetomidine on ED in children with sevoflurane anesthesia and to observe postoperative behavioral changes through long-term follow-up.MethodsPatients aged 2–7 years, American Society of Anesthesiologists class (ASA) I or II, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 28 publications
1
98
1
1
Order By: Relevance
“…A total of 24 RCTs were included in the present meta-analysis. [4][5][6][7][8][9][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The results showed that, compared with placebo, Dex was associated with positive effects on recovery quality in children undergoing general anaesthesia with sevoflurane, reducing nausea and vomiting and shortening the eye-opening time, extubation time, and duration of PACU stay. Unlike the present study, Amorim et al 10 reported that Dex reduced the incidence of emergence agitation while prolonging the duration of PACU stay and eye-opening time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 24 RCTs were included in the present meta-analysis. [4][5][6][7][8][9][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The results showed that, compared with placebo, Dex was associated with positive effects on recovery quality in children undergoing general anaesthesia with sevoflurane, reducing nausea and vomiting and shortening the eye-opening time, extubation time, and duration of PACU stay. Unlike the present study, Amorim et al 10 reported that Dex reduced the incidence of emergence agitation while prolonging the duration of PACU stay and eye-opening time.…”
Section: Discussionmentioning
confidence: 99%
“…35 Dex is a highly selective agonist of a-adrenergic receptors, having sedative, analgesic and anxiolytic effects at clinical doses without affecting the patient's breathing, 30 and it has been widely applied for anaesthesia in children. 7,8,36 Dex induces the activation of a2 receptors and stimulates blue-spot receptors, which can then affect the endogenous sleep pathway, mimicking the sedation that occurs in natural sleep. 37,38 Furthermore, a2 receptors in the spinal cord can also have certain analgesic effects, which will improve the recovery quality after general anaesthesia, probably by mainly reducing the occurrence of agitation during recovery.…”
Section: Discussionmentioning
confidence: 99%
“…A select few patients may end up having emergence delirium with the risk being higher in pediatric age groups and the elderly population. The incidence has been reported up to 80% in pediatric age group and this can increase risk of postoperative respiratory depression and airway obstruction [26].…”
Section: Emergence Deliriummentioning
confidence: 99%
“…Postoperative maladaptive behaviors have also been associated with preoperative distress (Fortier & Kain, 2015;Hayhoe et al, 2016). The most common postoperative maladaptive behaviors observed in children include nighttime crying, enuresis, separation anxiety, nightmares, apathy, withdrawal, decreased appetite, thrashing, and inconsolability (Harbaugh & Gadepalli, 2019;Rosenbaum, Kain, Larsson, Lönnqvist, & Wolf, 2009;Shi et al, 2019). These negative behaviors are believed to decrease over time; however, Kain, Mayes, Wang, and Hofstadter (1999) found that 67% of the children developed new maladaptive behaviors the day after surgery, 45% displayed these behaviors on day two after surgery, and 23% of them at two weeks after surgery.…”
Section: Review Of the Literaturementioning
confidence: 99%